Foreign policy in a changing multi-faceted global milieu: Revisiting the political-economic interface - Charokopos, Michael (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2018)
The emergence of new influential global actors and the seeming omnipotence of global markets have produced a highly diversified international environment challenging the concept of foreign policy and the theoretical contribution of FPA. In view of this challenge, it is argued that instead of considering the above changes through a fragmentary approach, it would be more efficient to conceive them as part of an ongoing transformation process governing practice and theory in foreign policy. On this background, the political-economic interface is revisited, in order to highlight the significance of the concepts of security and prosperity in the contemporary international framework and to reconsider the question of an interdisciplinary approach to foreign policy.